1987
DOI: 10.1111/j.1834-7819.1987.tb01850.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular joint ankylosis

Abstract: The reconstruction of a permanent functional joint and the provision for correction of any associated deformity are the aims of treatment of temporomandibular joint ankylosis. Methods which merely free the ankylosis, in our opinion, compromise the likelihood of achieving these aims.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(8 citation statements)
references
References 7 publications
0
7
1
Order By: Relevance
“…Most interesting is the reported overgrowth of the graft (Ellis et al, 2002). Many studies reported on the transplantation of 1-2 cm of cartilage with the costochondral graft when replacing the mandibular condyle (Rowe, 1982;Figueroa et al, 1984;Munro et al, 1986;Tideman and Doddridge, 1987). It is hypothesized that overgrowth of the mandible following costochondral grafting occurred because of transplantation of excessive amounts of cartilage (Copray et al, 1986;Peltomäki and Rönning, 1991;Peltomäki, 1992;Svensson and Adell, 1998;Ellis et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Most interesting is the reported overgrowth of the graft (Ellis et al, 2002). Many studies reported on the transplantation of 1-2 cm of cartilage with the costochondral graft when replacing the mandibular condyle (Rowe, 1982;Figueroa et al, 1984;Munro et al, 1986;Tideman and Doddridge, 1987). It is hypothesized that overgrowth of the mandible following costochondral grafting occurred because of transplantation of excessive amounts of cartilage (Copray et al, 1986;Peltomäki and Rönning, 1991;Peltomäki, 1992;Svensson and Adell, 1998;Ellis et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Most incidents of TMJ ankylosis occur after a trauma or an infection. Cases of congenital TMJ ankylosis are relatively rare, representing about 3% of TMJ ankylosis incidents (Converse, 1979;Tideman and Doddridge, 1987;Komorowska, 1997;Ajike et al, 2007;Mortazavi and Motamedi, 2007). However, little is known about genetic alterations that cause congenital TMJ ankylosis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the age of patients' when exposed to injury is an important factor in the assessment of maxillofacial deformities particularly in ankylosis of the TMJ. When children, especially below the age of 5 years are exposed to these injuries, it results in defective osteogenesis of the damaged cartilage of the mandibular condyle by the ankylotic process, and also in the loss of muscular guidance over mandibular growth process resulting in severe facial deformity [19,20]. As a consequence of this, patients present with severe maxillofacial alteration that will lead to TMJ ankylosis.…”
Section: Discussionmentioning
confidence: 99%